Two new species of Megalota from the Bahamas (Lepidoptera: Tortricidae: Olethruetinae) - Brown, John W.; Matthews, Deborah L.; Miller, Jacqueline Y. (Zootaxa, 2018)
Two new species of Megalota Diakonoff, 1966 are described and illustrated from the Bahamas: M. bahamana Brown & Matthews, new species, and M. insularis Brown and Matthews, new species. The two are among the 65 or so species of Tortricidae recorded from the Bahamas during an inventory of the Lepidoptera of the archipelago initiated in 2010.